An Analysis of Translation Acceptability in Translating Humour About Pun - Iftahur Rezqi; Havid Ardi (Universitas Negeri Padang, 2022)
This research was intended to find out the translation acceptability made by English department students about pun in humour text. this research is descriptive qualitative research. The subject of this research were students of translation class, selected by using cluster random sampling techniques. The technique of data collection was using translation test. The finding of the student acceptability was scored by using Nababan’s TQA model. the result of this research show that students’ translation in translating pun as humour were mostly in less acceptable.